Growth Performance, Immune Response, Antioxidative Status, and Antiparasitic and Antibacterial Capacity of the Nile Tilapia (Oreochromis niloticus) After Dietary Supplementation With Bottle Gourd (Lagenaria siceraria, Molina) Seed Powder - Radwan, Mahmoud; Abbas, Mahmoud Mahrous M.; Mohammadein, Amaal; Al Malki, Jamila S.; Elraey, Said M. A.; Magdy, Mohammad (Frontiers in Marine Science, 2022)
Medicinal plants are a potential safe source of bioactive compounds. Fish diet supplemented with the medicinal plant bottle gourd (Lagenaria siceraria) seed powder was evaluated in this study for the potential effect on growth performance, antioxidative status, immunological response, and resistance to infectious pathogens in the Nile tilapia (Oreochromis niloticus). Nile tilapia fingerlings with mean weight (±SD)= 25.64 ± 0.17 g), were fed four L. siceraria seed supplemented diets (LSSD) at 0.0, 1, 2, and 3 % for 60 days. Specimens were then challenged with the bacterium Aeromonas hydrophila for 10 days. Also, three different concentrations (2.5, 5, and 10 ml/L) of Lagenaria siceraria ethanolic extract (LSEE) were tested for their antibacterial and antiparasitic efficacy on four selected bacterial and one parasitic species. All parameters’ values generally improved with elevating the content of the L. siceraria seed powder in the diet. Dietary administration of LSSD-3 % enabled significant (P < 0.05) higher growth performance, and feed utilization efficiency. It reduced the mortality induced by A. hydrophila infection, increased crude protein content in the fish body and exhibited the highest in vitro antibacterial and antiparasitic efficiency. RBCs, WBCs, Hb, PCV, MCV, MCH, and total serum protein values in pre- and post-challenge groups, were significantly higher (P < 0.05) in the LSSD-3 % group. While MCHC, ALT, AST and glucose levels were significantly lower (P < 0.05) than those of the other groups. Lysozyme and antioxidant enzyme activities in pre- and post-challenge groups were also higher (P < 0.05) in the LSSD-3 % group compared to the other groups. LSEE provided good efficacy against Gram-negative bacterial strains, mild efficacy against Gram-positive bacterial strains, and an antagonistic effect on the parasite Cichlidogyrus Tilapiae. The 10 ml/L concentration was the most effective against the pathogens followed by the 5 ml/L concentration and then 2.5 ml/L. Our findings suggest the feasibility of supplementation of Nile tilapia (O. niloticus) diet with L. siceraria seed powder by 3% to improve the growth performance, immunity, and vital parameters.